Agility measurement index: A metric for the crossroads of software development methodologies - DATTA, Subhajit (Institutional Knowledge at Singapore Management University, 2006)
Software engineering's journey to maturity has been marked by the advent of different development methodologies. While each paradigm has its context and cognoscenti, project teams are often faced with the choice of one approach over another in the grind of delivering software on time and within budget. In this paper, we briefly review the three major techniques of addressing enterprise software development, namely the Waterfall, Unified and Extreme styles. The metric Agility Measurement Index is then proposed, which helps organizations choose the methodology that best suites a particular project.